2021
DOI: 10.1002/suco.202000783
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion assessment of ferrocement element with nanogeopolymer for marine application

Abstract: Corrosion is the major reason which limits the practical application of ferrocement structures in the marine environment. To protect the thin and strong wire mesh reinforcement, preventive methods are required to be employed. One of such methods implemented in this paper is novel application of geopolymer mortar on the surface of the wire mesh. The microstructural pores present in the highly durable fly ash based geopolymer mortar are further enhanced by using nanomodified fly ash particles to achieve the impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…While placing the coated rebar in the salt container for 30 days, it was observed that the coating attributed to lesser weight loss than the uncoated rebar. Similarly, Rajendran [11] conducted an experimental investigation to protect the meshing reinforcement of ferrocement panels from corrosion by incorporating nano-modifed fy ash-based geopolymer mortar. Te use of nano-geopolymer mortar on the ferrocement meshes ofers 3 times improved corrosion resistant behaviour and it was suggested mainly for marine applications.…”
Section: Introductionmentioning
confidence: 99%
“…While placing the coated rebar in the salt container for 30 days, it was observed that the coating attributed to lesser weight loss than the uncoated rebar. Similarly, Rajendran [11] conducted an experimental investigation to protect the meshing reinforcement of ferrocement panels from corrosion by incorporating nano-modifed fy ash-based geopolymer mortar. Te use of nano-geopolymer mortar on the ferrocement meshes ofers 3 times improved corrosion resistant behaviour and it was suggested mainly for marine applications.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of alkaline solution molarity on crack propagation and corrosion behavior of geopolymer mortar covering steel mesh for marine environments [145]. The effect of calcium and alkalinity on the chloride diffusivity of geopolymer mortar [146].…”
mentioning
confidence: 99%